2012
DOI: 10.2223/jped.2154
|View full text |Cite
|
Sign up to set email alerts
|

Which women breastfeed for 2 years or more?

Abstract: Objective: To identify factors associated with continuation of breastfeeding for 2 years or more.Methods: This was a cohort study that followed 151 children recruited at the Hospital de Clínicas in Porto Alegre, Brazil, from birth until ages ranging from 3 to 5 years. Mothers were interviewed in person in the maternity unit, at 7 and 30 days after delivery, and when their children were from 3 to 5 years old. Interviews were also conducted at 60, 120 and 180 days, by telephone when possible, or during a home vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
13

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 23 publications
3
30
0
13
Order By: Relevance
“…It is known that this practice may be associated to early ablactation according to a cohort study conducted in the city of Porto Alegre, Rio Grande do Sul, which concluded that postponing the introduction of water and/or teas, as well as other types of milk, increased the chance of breastfeeding for over two years. (18) Regarding the feeding of the children older than six months it was verified that all of them were subject to supplemented breastfeeding, as were the infants in the Nawa and Nukini ethnicities.…”
Section: Breastfeeding In the Katukina Ethnic Groupmentioning
confidence: 98%
“…It is known that this practice may be associated to early ablactation according to a cohort study conducted in the city of Porto Alegre, Rio Grande do Sul, which concluded that postponing the introduction of water and/or teas, as well as other types of milk, increased the chance of breastfeeding for over two years. (18) Regarding the feeding of the children older than six months it was verified that all of them were subject to supplemented breastfeeding, as were the infants in the Nawa and Nukini ethnicities.…”
Section: Breastfeeding In the Katukina Ethnic Groupmentioning
confidence: 98%
“…In India, living in a rural area and maternal unemployment were found to be associated with longer breastfeeding duration 4 . In Brazil, mothers staying at home with their children during the first six months of life, not using a pacifier, and the later introduction of water, teas or other types of milk were variables associated with breastfeeding up to two years of age or beyond 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The energy and nutrient content of breast milk is adequate for the physiological immaturity of the infant, and its ability to protect against gastrointestinal and respiratory diseases make breast milk the ideal food capable of meeting the nutritional needs of the infant, especially during the first months of life of the child and promote the child's full development 1, 3,5,7,31 . Some health professionals cite these biological factors and many contents disclosed by the media, making explicit the benefits of breastfeeding and evident the preventive aspects for the child 7,10,12 .…”
Section: The Importance Of Breastfeeding For the Health And Nutritionmentioning
confidence: 99%